KEBIASAAN OLAH RAGA BERPENGARUH TERHADAP TINGKAT STRESS MAHASISWA POLTEKKES KEMENKES JAKARTA III - Ricca Andalasari; Abdurahman Berbudi BL (Jurnal Ilmu dan Teknologi Kesehatan, 2018)
Health is something everyone needs, but with a solid activity we sometimes forget to maintain health, and more often ignore it. To maintain health we must do exercise, good exercise will increase endorphin hormone, and decrease cortisol, which affects a person's stress level, good exercise habits will decrease a person's stress level. The purpose of this study is to determine the relationship of exercise habits to stress levels of the students Poltekkes Kemenkes Jakarta III. Sampling Method using purposive random sampling, and the design study used is crossectional design. There were 100 students participated in tjis study. The results of this study found that exercise habits of stress levels have a high relationship, and significant influence where obtained p value <0.05. This shows that good sports habits affect the level of stress in students Poltekkes Kemenkes Jakarta III